Alojzija Štebi, "Mišljenje javnosti i feminizam u Jugoslaviji" (Public Opinion and Feminism in Yugoslavia): Ženski pokret [Women's Movement] 9 (1924), 376–379. Issue 1 (1st June 2022) - Grubački, Isidora
Abstract: This contribution is a translation of a speech given by the president of the Yugoslav Feminist Alliance, Alojzija Štebi, to the second conference of the Little Entente of Women (LEW) in Belgrade in 1924. The introduction contextualizes the source, introduces Alojzija Štebi through a biographical note, and offers a glimpse into Yugoslav women's participation in the Little Entente of Women. It shows that Štebi's conceptualization of feminism was inseparable from politics, called for political reform, and invited the members of the LEW to move toward the full-scale participation of women in politics and state affairs.